THE EFFECT OF IMPLEMENTATION PROJECT BASED LEARNING (PJBL) MODEL ON STUDENTS' MATHEMATICS LEARNING OUTCOMES IN GRADE IV AT UPTD SD NEGERI 1 WERU LOR - Nur Laeli Asifah; Sati; Hema Widiawati (Jurnal Cakrawala Pendas, 2025)
This research is motivated by the results of observations and interviews with homeroom teachers which indicate that the mathematics learning outcomes of fourth-grade students at UPTD SD Negeri 1 Weru Lor, Weru District, Cirebon Regency are still relatively low. This is because learning is still teacher-centered, the learning model is less innovative, the learning methods are less varied, and the use of learning media is not used. Thus, students are less able to analyze, conclude, and create concepts for data analysis and opportunities for data presentation materials in the form of bar charts. Therefore, the purpose of this study is to determine the effect of the implementation of the Project Based Learning (PjBL) model on students' mathematics learning outcomes. This study uses a quantitative method with a research design, namely a pre-experimental type one group pretest posttest. The sample of this study, namely 24 fourth-grade students selected through a total sampling technique. The research instruments are observation sheets and learning outcome tests. The results of the study show a significant increase before and after the implementation of the Project Based Learning (PjBL) model, including aspects of teaching modules, teacher performance, learning outcomes (cognitive, affective, and psychomotor). This can be proven by the results of the hypothesis test which obtained a t-count of 65.987 and a significance value of 0.000. Thus, it can be concluded that the application of the Project Based Learning (PjBL) model has an effect on student learning outcomes in mathematics learning in grade IV of UPTD SD Negeri 1 Weru Lor.